PENGETAHUAN ORANG TUA TENTANG JAJANAN SEHAT PADA ANAK - Mega Oktaviana; Ririn Nasriati; Rika Maya Sari (Universitas Muhammadiyah Ponorogo, 2018)
AbstractSnacks had important role in providing energi and nutrition for children. But, the level of snacks safeties were concerned. Therefor, the snacks that were consumed by children need special attention for parents. The knowledge of parents were very influence for the children snacks habbit. The research objective was to knew the parentss knowledge about the healthy snacks on children.This research design was descriptive with a population of 252 parents at Bajang Village Mlarak District Ponorogo Regency. The sample were 63 respondents and the research method that used was purposive sampling. The data were collected by questionnaires and displayed with precentage.The results of this research indicate that from 63 respondents obtained the enough knowledge were 31 respondents (49%),the less knowledge were 22 respondents (35%), the good knowledge were 10 respondents (16%) about the healthy snacksBased on the results of research itcould be concluded that almost a half of respondents were knowledgeable enough about the healthy snacks. Hopefully the parents are expected to incrase knowledge about healthy snacks with a lot af reading print media or electronic media and actively asked the health workers so the parents could changed the life behaviour and more understand about the healthy snacks which wree good for children.Keywords: Knowledge, Parents, Healthy SnacksAbstrak Jajanan memegang peranan yang cukup penting dalam memberikan asupan energi san gizi bagi anak khususnya usia sekolah. Akan tetapi, tingkat keamanan jajanan sekarang ini cukup memprihatinkan. Oleh karena itu jajanan yang dikonsumsi anak perlu menjadi perhatian khusus bagi para orang tua. Pengetahuan orang tua sangat mempengaruhi kebiasaan jajan anak. Penelitian ini bertujuan untuk mengetahui pengetahuan orang tua tentang jajanan sehat pada anak. Desain penelitian ini adalah deskriptif dengan populasi adalah 252 orang tua di Desa Bajang Kecamatan Mlarak Kabupaten Ponorogo. Besar sampel 63 responden dan metode penelitian menggunakan purposive sampling. Pengumpulan data menggunakan kuesioner data ditampilkan dengan prosentase. Hasil penelitian menunjukkan bahwa dari 63 responden didapatkan hasil pengetahuan cukup 31 responden (49%), pengetahuan kurang 22 responden (35%), pengetahuan baik 10 responden (16%) tentang jajanan sehat. Berdasarkan hasil penelitian dapat disimpulkan bahwa hampir setengahnya responden berpengetahuan cukup tentang jajanan sehat. Diharapkan untuk para orang tua untuk untuk menambah pengetahuan tentang jajanan sehat dengan banyak membaca media cetak atau media elektronik dan aktif bertanya kepada petugas kesehatan agar para orang tua dapat merubah perilaku hidup dan lebih memahami mengenai jajanan sehat yang baik dokonsumsi untuk anak.Kata Kunci :Pengetahuan, Orang Tua, Jajanan Sehat